9.6k views
4 votes
If f(x) =3x^2 +1 and g(x) = 1 -x, what is the value of (f-g) (2)?

User Bluecakes
by
5.0k points

2 Answers

3 votes

Answer:

14

Explanation:

(f-g)(2) means f of x minus g of x when x equals 2.

To solve, first set up the equation


(3x^2}+1)-(1-x)

Change the signs in the second part. {because this is subtraction}


3x^2}+1-1+x

Replace x with 2.


3(2^2})+1-1+2

Solve.


3(4)+2


12+2


14

User Stanleyerror
by
4.7k points
5 votes

Answer:

(f-g)(2) = 14

Explanation:

f(x) =3x^2 +1 and g(x) = 1 -x

f(2) = 3(2)^2 +1 = 3(4)+1 = 12+1 = 13

g(2) = 1-2 = -1

f(2) - g(2) = 13 - -1 = 13+1 =14

User Fieldingmellish
by
4.8k points